Development of tactical decision-making skills in youth soccer players: Macro- and microstructure of soccer developmental activities as a discriminant of different skill levels - Machado, G.; González-Víllora, S.; Sarmento, H.; Teoldo, I. (International Journal of Performance Analysis in Sport, 2020)
Decision-making in soccer is considered an important factor for soccer players achieve high-performance level. Studies in several sports indicated that tactical decision-making skills are necessary for skilful performance. We aimed to analyse whether soccer players with different levels of decision-making skills can be differentiated based on their engagement in various types and amounts of soccer activities during their development. The sample comprised 149 Brazilian youth male soccer players (M = 14.9, SD = 1.6 years). We examined the type and amount of soccer activities that contributed to distinguish players with different levels of offensive and defensive decision-making skills. Players` tactical decision-making skills were assessed with an objective video-based test (TacticUP® video test for soccer). We used a retrospective questionnaire to collect information about previous participation in different soccer developmental activities. The main activities that differentiated high/low skill groups in the macrostructure activities were: i) team practice; and in the microstructure: ii) collective tactics; and iii) "high decision-making opportunities". We concluded that previous soccer developmental activities discriminate youth soccer players with different levels of decision-making skills. The main activities that differentiated high/low groups were: 1) team practice; 2) collective tactics in team practice, and; 3) "high decision-making opportunities" in team practice.